2022
DOI: 10.1101/2022.04.12.22273722
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measures for infection prevention and control of SARS-CoV-2 in Belgian schools between December 2020 and June 2021: a prospective cohort study

Abstract: Introduction: As the role of school-aged children was unclear at the onset of the COVID-19 pandemic, public health authorities recommended to implement infection prevention and control (IPC) measures in school settings. Few studies evaluated the implementation of these measures and their effect on SARS-CoV-2 infection rates among pupils and staff. Aim: To describe the implementation of IPC measures in Belgian primary and secondary schools and assess its relation to the prevalence of anti-SARS-CoV-2 antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…In the present study SARS-CoV-2 infection was equally present among adults and children, consistent with findings from previous studies [7, 10, 22]. We found no significant difference in the proportion of asymptomatic cases between children and adults during the second part of the study, while it was observed that children were more often asymptomatic during September – December 2020 [10].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study SARS-CoV-2 infection was equally present among adults and children, consistent with findings from previous studies [7, 10, 22]. We found no significant difference in the proportion of asymptomatic cases between children and adults during the second part of the study, while it was observed that children were more often asymptomatic during September – December 2020 [10].…”
Section: Discussionsupporting
confidence: 92%
“…In addition to structural interventions such as improving air quality in schools through better ventilation systems [6, 7], screening protocols such as repetitive and reactive screening can also aid in preventing the occurrence of large school outbreaks and consequent closures. In reactive screening, a classroom is tested and quarantined after a certain number of cases is observed, whereas in repetitive screening the entire classroom is tested regularly, regardless of whether a case is observed or not.…”
Section: Introductionmentioning
confidence: 99%
“…To have the most relevant comparison, we only used the reported seroprevalence collected from persons living in the same geographic region as our patients and filtered on data collected during the same period as our study. Estimated seroprevalence from healthy children was obtained from longitudinal studies in Belgian schools (16)(17)(18)(19), which used a validated serology test in saliva (20). We only used data from pupils from Flemish primary schools to ensure demographic matching with our cohort (these pupils were non-vaccinated during the entire study period).…”
Section: Serological Data Collectionmentioning
confidence: 99%
“…None had known primary or secondary immune deficiency. To compare our pediatric data, a surveillance study measuring seroconversion in pupils from schools is plotted (green) (16)(17)(18)(19). For this healthy pediatric cohort, we used the readily available and substratified data from the subnational level (Flanders) and concerning children from primary school, to maximally match our cohort of patients.…”
Section: Evolution Of Seropositivity In the Cohortmentioning
confidence: 99%